Trial of Green Chemistry-Based Chemistry Laboratory Manual on Acid-Base Indicators - Nurlaili; Usman; Aldiansyah; Muhammad Febry; Yuli Hartati (Universitas Pendidikan Mandalika, 2025)
Chemistry laboratory experiments often use hazardous chemicals that can pose health risks and cause environmental damage. Green chemistry-based chemistry experiments are important because they use materials that are safe for students and the environment. Unlike previous laboratory manuals, this manual integrates green chemistry principles and digital features to enhance student independence. The purpose of this study was to examine the practicality and effectiveness of the green chemistry-based chemistry practicum guide on acid-base indicator material. This study was a Research and Development (R&D) study using the Borg and Gall model. This study focused only on the limited trial stage, initial product revision, and field trials to test the practicality and effectiveness of the Practicum Guide. Data collection techniques used questionnaires to determine practicality scores and N-Gain tests for effectiveness. The results of the practicality score analysis of the green chemistry-based chemistry practicum guide for teachers were in the very practical category, while students were in the practical category, reinforced by the results of observations of teacher and student activities in the very good category. The results of the analysis of the effectiveness of the green chemistry-based chemistry Practicum Guide using N-Gain were in the moderate category. Thus, this chemistry Practicum Guide is practical and effective for use in simple acid-base indicator practicums.